Using Technology to Enhance Students’ Attention and Participation in Basic Language Courses at CIEX: Thesis Background Issues - Dueñas, Daniel; Castillo, Maria (CIEX JOURNAL, 2016)
This article presents the design of a study about the effects of using technology for English language teaching and learning purposes among basic level courses students as a tool for enhancing their interest to the classes at CIEX, a private foreign language center located in Chilpancingo, Guerrero, Mexico. Specifically, the study aims to identify what is the relation between students’ attention and participation, and the use of technology in Basic English classes. The study also addresses: (a) whether the inclusion of technology in the English classes actually gets more results and more attention and participation from the students than other traditional means; (b) the teachers’ perceptions about the idea that the previous English teaching theories and teaching methods can be replaced by new ones that include the application of the technology in order to get better advances in the students’ learning; (c) the students’ attitudes towards the use of technology in a Basic English class and how they feel about using technology for their English language learning; and (d) whether the students prefer to use technology in the class rather than the traditional materials. It is important to mention that in this article only the design of the study will be described.